MWCNT‐Organoimido Polyoxomolybdate Hybrid Material: Analytical Applications for Amperometric Sensing of Hydrogen Peroxide. Issue 9 (26th May 2021) - Mujica, Michael López; Sotomayor‐Santander, Ilania; Hermosilla‐Ibáñez, Patricio; Oyarzun‐Ampuero, Felipe; Rodríguez, Marcela C.; Rivas, Gustavo A.; Venegas‐Yazigi, Diego; Bollo, Soledad
Abstract: We report a hybrid material obtained by dispersing the polyoxometalate n‐[Bu4 ‐N]2 [Mo6 O18 NC13 H9 ] functionalized with 2‐aminofluorene (POMAF) and multi‐walled carbon nanotubes (MWCNTs) in 1, 3‐dioxolane (MWCNT‐ POMAF). We demonstrate the peroxidase‐like activity of the hybrid material and its application for the amperometric quantification of hydrogen peroxide at −0.450 V previous drop‐coating at glassy carbon electrodes, with a linear range between 1.0 μM and 6.0 μM and a detection limit of 330 nM. The reproducibility was 2.2 % using one MWCNTs‐POMAF dispersion, and 3.9 % using 4 different dispersions. The sensor was successfully used for the quantification of hydrogen peroxide in enriched milk samples. Abstract :